2012
DOI: 10.1585/pfr.7.2403117
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Formation of Helical Structures in Reversed-Field Pinch

Abstract: Nonlinear three-dimensional magnetohydrodynamic(MHD) simulations were applied to a reversed-field pinch(RFP) plasma to reveal the physical mechanism of the formation of helical structures such as the so-called quasi-single helicity and single helical axis states. The simulations were executed using the MHD Infrastructure for Plasma Simulation (MIPS) code in a realistic experimental geometry of the REversed field pinch of Low-Aspect ratio eXperiment (RELAX) device with reconstructed initial equilibria calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The toroidal mode number n may be four. Previous research using nonlinear MHD simulations indicated that the plasma would deform into helical structures with (m, n) = (1, −4) [9], which is consistent with the magnetic field measurements. While more detailed investigations are required, the obtained profiles show periodicity, which may be correlated to magnetic field fluctuations.…”
Section: Discussionsupporting
confidence: 86%
“…The toroidal mode number n may be four. Previous research using nonlinear MHD simulations indicated that the plasma would deform into helical structures with (m, n) = (1, −4) [9], which is consistent with the magnetic field measurements. While more detailed investigations are required, the obtained profiles show periodicity, which may be correlated to magnetic field fluctuations.…”
Section: Discussionsupporting
confidence: 86%
“…Ideal MHD equilibrium solvers allow the reproduction of QSH equilibria [26], but need experimental input such as the position of the helical axis, pressure profile and safetyfactor profile. Three-dimensional codes solving the MHD equations in toroidal geometries without a priori definition of pressure and safety-factor profiles exist, [24,27,28] but there is not yet, to our knowledge, a study which systematically investigates the influence of curvature on the dynamics of a toroidal magnetofluid in the RFP context. This motivates the present study which compares, using exactly the same numerical code and governing equations, the dynamics of a viscoresistive magnetofluid in a toroidal domain to those in a cylindrical domain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in some recent RFP investigations, the pressure is retained (Mizuguchi et al. 2012) and recently we focused on the importance of the pressure dynamics (Chahine & Bos 2018). In particular, we illustrated in MHD simulations in cylindrical geometry that, to understand the dynamics of the plasma, the important quantity to monitor is not the pressure but its gradient.…”
Section: Equations Numerical Methods and Parametersmentioning
confidence: 99%